Isolevuglandin-Modified Cardiac Proteins Drive CD4+ T-Cell Activation in the Heart and Promote Cardiac Dysfunction. Issue 12 (19th January 2021) - Ngwenyama, Njabulo; Kirabo, Annet; Aronovitz, Mark; Velázquez, Francisco; Carrillo-Salinas, Francisco; Salvador, Ane M.; Nevers, Tania; Amarnath, Venkataraman; Tai, Albert; Blanton, Robert M.; Harrison, David G.; Alcaide, Pilar
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Despite the well-established association between T-cell–mediated inflammation and nonischemic heart failure, the specific mechanisms triggering T-cell activation during the progression of heart failure and the antigens involved are poorly understood. We hypothesized that myocardial oxidative stress induces the formation of isolevuglandin (IsoLG)–modified proteins that function as cardiac neoantigens to elicit CD4+ T-cell receptor (TCR) activation and promote heart failure. Methods: We used transverse aortic constriction in mice to trigger myocardial oxidative stress and T-cell infiltration. We profiled the TCR repertoire by mRNA sequencing of intramyocardial activated CD4+ T cells in Nur77 GFP reporter mice, which transiently express GFP on TCR engagement. We assessed the role of antigen presentation and TCR specificity in the development of cardiac dysfunction using antigen presentation–deficient MhcII −/− mice and TCR transgenic OTII mice that lack specificity for endogenous antigens. We detected IsoLG protein adducts in failing human hearts. We also evaluated the role of reactive oxygen species and IsoLGs in eliciting T-cell immune responses in vivo by treating mice with the antioxidant TEMPOL and the IsoLG scavenger 2-hydroxybenzylamine during transverse aortic constriction, and ex vivo in mechanistic studies of CD4+ T-cell proliferation in response to IsoLG-modified cardiac proteins. Results: We discovered that TCR antigen recognition increases in the left ventricle as cardiac dysfunction progresses and identified a limited repertoire of activated CD4+ T-cell clonotypes in the left ventricle. Antigen presentation of endogenous antigens was required to develop cardiac dysfunction because MhcII −/− mice reconstituted with CD4+ T cells and OTII mice immunized with their cognate antigen were protected from transverse aortic constriction–induced cardiac dysfunction despite the presence of left ventricle–infiltrated CD4+ T cells. Scavenging IsoLGs with 2-hydroxybenzylamine reduced TCR activation and prevented cardiac dysfunction. Mechanistically, cardiac pressure overload resulted in reactive oxygen species–dependent dendritic cell accumulation of IsoLG protein adducts, which induced robust CD4+ T-cell proliferation. Conclusions: Our study demonstrates an important role of reactive oxygen species–induced formation of IsoLG-modified cardiac neoantigens that lead to TCR-dependent CD4+ T-cell activation within the heart.